2012
DOI: 10.1186/2110-5820-2-42
|View full text |Cite
|
Sign up to set email alerts
|

Management of thrombocytopenia in the ICU (pregnancy excluded)

Abstract: Thrombocytopenia is a very frequent disorder in the intensive care unit. Many etiologies should be searched, and therapeutic approaches differ according to these different causes. However, no guideline exists regarding optimum practices for these situations in critically ill patients. We present recommendations for the management of thrombocytopenia in intensive care unit, excluding pregnancy, developed by an expert group of the French-Language Society of Intensive Care (Société de Réanimation de Langue França… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…The majority of patients were male (n = 125, 70%) and the mean age was 63 years (median: 69; interquartile range: 51-78 years) ( Table 1). Median APACHE II score was 16 (interquartile range: [12][13][14][15][16][17][18][19][20][21][22] and median length of time in the ICU was 10.5 days (interquartile range: 5-17 days). Mechanical ventilation was used on 149 patients (84%) for a median length of six days (interquartile range: 2-11 days).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of patients were male (n = 125, 70%) and the mean age was 63 years (median: 69; interquartile range: 51-78 years) ( Table 1). Median APACHE II score was 16 (interquartile range: [12][13][14][15][16][17][18][19][20][21][22] and median length of time in the ICU was 10.5 days (interquartile range: 5-17 days). Mechanical ventilation was used on 149 patients (84%) for a median length of six days (interquartile range: 2-11 days).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, the role of immature platelets to indicate the mechanism of thrombocytopenia is well recognised [4][5][6][7][8][9][10] due to its ability to differentiate central and peripheral thrombocytopenias [31]. In 2012, an expert group published recommendations for the management of thrombocytopenia and strongly agreed that decisions to treat thrombocytopenia should consider, amongst other factors, mechanisms of thrombocytopenia [43]. To this end, IPF has the potential to offer insight into the underlying mechanisms of thrombocytopenia, although there is no fundamental UK-based reference interval data currently available for IPF on the Sysmex XN-series analysers for the purpose of future research and potential clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, routine bone marrow aspiration is not recommended. However, bone marrow aspiration may be performed in cases of unknown cause and the presence of abnormalities of other blood cells [32]. Thiolliere et al [14]analyzed the results of bone marrow aspiration in 255 ICU patients and found that for patients with absolute thrombocytopenia, bone marrow aspiration showed (from more to less common) sepsis-related bone marrow features characterized by megakaryocyte depletion,normal bone marrow, folic acidand vitamin B12 deficiency-related changes, megaloblastosis, and hematological tumors.…”
Section: Recommendation 7: Comprehensive Laboratory Tests Aid In the mentioning
confidence: 99%